A study of thyroid functions in patients with Cushing's syndrome: a single-center experience. Issue 8 (August 2019) - Xiang, Boni; Tao, Ran; Liu, Xinhua; Zhu, Xiaoming; He, Min; Ma, Zengyi; Yang, Yehong; Zhang, Zhaoyun; Li, Yiming; Yao, Zhenwei; Wang, Yongfei; Ye, Hongying
Abstract : Objective: The aim of this study was to evaluate thyroid functions in Cushing's syndrome (CS), the dynamic changes of thyroid hormones and antithyroid antibodies in Cushing's disease (CD) pre- and postoperatively. Design and methods: This is a retrospective study enrolling 118 patients with CS (102 CD, 10 adrenal CS and 6 ectopic adrenocorticotropic syndrome (EAS)). Thyroid functions (thyroid-stimulation hormone (TSH), T3, free T3 (FT3), T4 and free T4 (FT4)) were measured in all CS at the time of diagnosis and in all CD 3 months after transsphenoidal pituitary tumor resection. Postoperative hormone monitoring within 3 months was conducted in 9 CD patients completing remission. Twenty-eight remitted CD patients experienced hormone and antithyroid antibody evaluation preoperatively and on the 3rd, 6th and 12th month after surgery. Results: TSH, T3 and FT3 were below the reference range in 31%, 69% and 44% of the 118 CS patients. Remitted CD patients (81/102) had significantly higher TSH ( P  = 0.000), T3 ( P  = 0.000) and FT3 ( P  = 0.000) than those in the non-remission group (21/102). After remission of CD, TSH, T3 and FT3 showed a significant increase, with a few cases above the reference range. By 12 months, most CD patients' thyroid functions returned to normal. Thyroid hormones (including TSH, T3 and FT3) were negatively associated with serum cortisol levels both before and after surgery. No significant changes of antithyroid autoantibodies were observed. Conclusions: TSH, T3 and FT3 are suppressed in endogenous hypercortisolemia. After remission of CD, TSH, T3 and FT3 increased significantly, even above the reference range, but returned to normal 1 year after surgery in most cases. Antithyroid antibodies did not change significantly after remission of CD.